GREEN CONSTITUTION SEBAGAI PENGUATAN NORMA HUKUM LINGKUNGAN DAN PEDOMAN LEGAL DRAFTING PERATURAN DAERAH DALAM RANGKA PRAKTIK-PRAKTIK TATA KELOLA PEMERINTAHAN YANG BAIK DI DAERAH - Ketut Rachmi Handayani, I Gusti Ayu (Faculty of Law, Universitas Sebelas Maret, 2012)
AbstractThe purpose of this study is to formulate legal drafting a model policy formulation Regional Regulation based Green Legislation in order to develop the practices of good governance in the region through strengthening the role of the executive (such as the leading sector of legal department Sector, BLH, Central Java Regional Environment and Parliament through strategies, mechanisms, and empowerment potential, and improving procedures for preparing regulations for environment conservation attention. This study is a juridical non-doctrinal, with a qualitative approach. The method will be used through the stages of: mapping the existing condition into the formulation of legal drafting which has been used, mapping of potential executive (leading sector) and the Parliament, to evaluate regulations that have been generated , identify and evaluate the constraints faced in the policy formulation stage, identify opportunities and strategies and formulate a model formulation that can be developed. The emphasis in the context of formulation of legal drafting by the Government to produce a green-based regulation legislation. The results of research are: First, the preparation of formulations Legal Drafting regulations made by the Government in accordance with Act No. 12 of 2011 and Act No. 32 of 2004, but not all use the Paper of Academic regulation in the formulation so that the Legal Drafting Regional Regulation not meet the criteria of a good legal system. Second, participation has not been effective and not all regulation is preceded Academic Paper. Third, the constraints in the formulation of legal drafting regulations include limitations of the preparation of draft environmental preservation, the ability to assess the regulation, the ability to formulate an explicit policy, concrete , clear and operational.